Clinical trials of lasers for toenail onychomycosis: The implications of new regulatory guidance. (3rd April 2017) - Gupta, Aditya K.; Foley, Kelly A.; Daigle, Deanne
Abstract: Background: Despite the fact that lasers are presently indicated for the cosmetic outcome "temporary increase in clear nail", these devices are increasingly used to treat onychomycosis and particularly in patients who are unwilling or unable to take oral antifungal medication. The US Food and Drug Administration (FDA) recently issued draft guidance for medical device trials for onychomycosis. Objective: This review evaluates the quality of laser trials for onychomycosis and compares the design guidelines for medical devices and antifungal drugs. Method: The PubMed database up to 29 May 2015 was searched for clinical studies of laser treatment for onychomycosis. Results: The evidence demonstrating that lasers eradicate pathogenic fungi is limited and published laser trials suffer from limitations such as incomplete reporting of randomization and lack of stratified analyzes for fingernail/toenail data and infecting organisms. Differences in inclusion criteria and efficacy outcomes between drug and device guidelines may prevent the comparison of results from device and drug trials. Conclusion: We propose the standardization of device guidelines to match those of antifungal drug trials. Patients and physicians need to be aware of the capabilities and limitations of laser treatment for onychomycosis.